Analisis Manajemen Pembiayaan Pendidikan di SMK Jawa Tengah: Studi Kasus Efektivitas Alokasi Dana bagi Siswa Ekonomi Lemah dalam Lembaga Semi-Militer - Umi Nur Wahidah; Nurul Anisatul Mufittah; Nindhita Ajeng Widowati; Aulia Sugma Majiida (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the effectiveness of educational financing management at Central Java State Vocational High Schools, especially in allocating funds for students from low-income families. The background of this study is based on the importance of an efficient, transparent, and targeted financing system in creating inclusive and quality education. This study uses a qualitative approach with a case study method and was conducted on April 25, 2025. Data were collected through interviews and reinforced by information from the school's official website. The results of the study indicate that budget planning and allocation have been systematically arranged based on the priority scale of student needs. However, the effectiveness of fund allocation in supporting superior programs still needs to be improved. Budget evaluations are carried out periodically, but do not yet include indicators of impact on student achievement and work readiness. Supervision is carried out internally and externally, but is still constrained by strict administrative procedures. This study suggests the need to strengthen the impact-based evaluation system and increase the flexibility of budget use policies to be more responsive to the real needs of students.